Perbedaan Penerapan Pembayaran Pajak Manual dan E-Billing Terhadap Penerimaan Pajak - Hana Puji Rahayu (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the existence of a significant difference between the level of tax receipts in the application of manually and the application of E-Billing at the Pratama Tax Office Bantul. The population in this study is the Tax Revenue report and the sample is a Tax Receipt report 30 days before the E-Billing payment is valid and 30 days after the E-Billing payment is applied. Data collection techniques are carried out by means of documentation and interviews. Data analysis techniques are carried out using descriptive statistical tests, normality tests and different tests Paired Sample T-Test using SPSS (Statistical Product and Services Solution) 16.0 for Windows. The results of the paired sample test different test results on the application of manual payment methods and E-Billing showed the value of Sig. (2-tailed) which is 0.003 smaller than the significance level of α 0.05 (0.003 <0.05) which means that there are significant differences in the Tax Revenue by applying manually and applying E-Billing at the Pratama Tax Service Office in Bantul. Keywords: Manual methods, E-Billing and Tax Revenue methods.